2019
DOI: 10.5334/egems.293
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Workflow and Substance Use Screening, Brief Intervention, and Referral to Treatment Data in the Electronic Health Records: A National Drug Abuse Treatment Clinical Trials Network Study

Abstract: Introduction: The use of electronic health records (EHR) data in research to inform recruitment and outcomes is considered a critical element for pragmatic studies. However, there is a lack of research on the availability of substance use disorder (SUD) treatment data in the EHR to inform research. Methods: This study recruited providers who used an EHR for patient care and whose facilities were affiliated with the National Institute on Drug Abuse’s National Drug Abuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, our analysis suggested that structured EHR data only documented 22.0% of screening results, consistent with the literature. 8–10 Despite its high performance, LRM alone was unable to capture substance use information comprehensively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our analysis suggested that structured EHR data only documented 22.0% of screening results, consistent with the literature. 8–10 Despite its high performance, LRM alone was unable to capture substance use information comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of pediatric healthcare systems have suggested that substance use screening with adolescents is occurring, but documentation in patients’ electronic health records (EHRs) is often unstandardized and exists in unstructured clinical notes, rather than in structured data fields. 8–10 The complexity and intensity of retrieving substance use screening information from unstructured data has limited healthcare systems in supporting providers as they monitor substance use over time. 8 , 11 , 12 Some studies have proposed incorporating standardized screening protocols to streamline documentation, 6 , 13 which, however, does not entirely address the challenges of modifying pediatrician behavior, 14 documentation, 8 or outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' healthcare data collected from EHRs and connected health IT tools have been used to measure the progress or outcomes of such efforts through quality improvement processes, meaningful use requirements, and research studies (Centers for Medicare & Medicaid Services [CMS], 2020; FDA, 2019; Krumholz et al, 2016). There is an urgent need to make SUD treatment-related information available in real-world patient data (Wu et al, 2019). The findings from this study emphasize the need to improve the completeness of SUD treatment data in EHRs; design individualized, user-specific interfaces to enhance the delivery of SBIRT services for SUDs via EHRs and connected IT tools; and develop research-friendly tools to integrate patient care data from multiple sources.…”
Section: Discussionmentioning
confidence: 99%
“…Only after effective clinical data recording tools are developed and integrated into a retrievable EHR system can effective pragmatic research be conducted. This survey highlights the ongoing variability in accessing complete information for SUD research through EHR systems (Wu et al, 2019).…”
Section: Summary Of Findingsmentioning
confidence: 99%